Developmental patterns of chimpanzee cerebral tissues provide important clues for understanding the remarkable enlargement of the human brain - Sakai, Tomoko (The Royal Society, 2013)
Developmental prolongation is thought to contribute to the remarkable brain enlargement observed in modern humans (Homo sapiens). However, the developmental trajectories of cerebral tissues have not been explored in chimpanzees (Pan troglodytes), even though they are our closest living relatives. To address this lack of information, the development of cerebral tissues was tracked in growing chimpanzees during infancy and the juvenile stage, using three-dimensional magnetic resonance imaging and compared with that of humans and rhesus macaques (Macaca mulatta). Overall, cerebral development in chimpanzees demonstrated less maturity and a more protracted course during prepuberty, as observed in humans but not in macaques. However, the rapid increase in cerebral total volume and proportional dynamic change in the cerebral tissue in humans during early infancy, when white matter volume increases dramatically, did not occur in chimpanzees. A dynamic reorganization of cerebral tissues of the brain during early infancy, driven mainly by enhancement of neuronal connectivity, is likely to have emerged in the human lineage after the split between humans and chimpanzees and to have promoted the increase in brain volume in humans. Our findings may lead to powerful insights into the ontogenetic mechanism underlying human brain enlargement.